PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MENANGANI PENGUNGSI VENEZUELA DI KOLOMBIA PADA TAHUN 2018-2020 - Anggun Chairunisyah; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the role of united nations high commisioner for refugees (UNHCR) in dealing with venezuelan refugees in Colombia and explain what efforts have been made by UNHCR to help deal with the venezuelan refugees in Colombia 2018 - 2020. The type of this research is descriptive analytic method. Descriptive method is a method that tries to collect, compile, interpret data which is then proposed by analyzing the data. Technique of data analyze is qualitative and use secondary is obtained from books, journals, official websites with valid sources. The author uses a pluralism perspective and a level group analysis. And the theory used in this research is the theory of the role of international organization by Magandar Situmorang. The result of this study indicated, the role of UNHCR in dealing with venezuelan refugee in colombia was to act as an facilitator and initiator. As the facilitator of UNHCR facilitated the collaboration between the Colombian government and other organizations. Then as the initiator of UNHCR brought the issue of refugees to the international community as a disseminator of information through the (RRMP) program.Keywords: Role, UNHCR, Refugees, Pluralism Perspective,  Group Analysis